Traceability System Model for Quality Gelatin Raw Material of Cattle Hides - Nur, S; Munandar, JM; Machfud, Machfud (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
Several criteria must be accomplished within the provision of quality products in terms of the types of materials, the processing methods and effort to get it. Traceability system involves various parties that have different needs and goals in the process of supplying raw materials.Â Hence, there is a need for institutional systems engineering that can organize and manage the tracking process, the procurement of raw materials that guarantee the origin of gelatin raw materials, and facilitate the industry and customer to create a standardized quality of product. The purpose of the study formulates the institutional tracking models of gelatin raw material from cattle hide based on various criteria and assessment of the expert opinion. The methods used in this study were Interpretative structural modeling to formulate a representation of institutional tracking efficiently and analytical hierarchy process to determine the tracking strategy of industrial gelatin raw materials from cowhide. The results obtained from the study were some key elements of institutional tracking model for industrial gelatin raw materials from cowhide and the traceability strategies for industrial raw materials from cattle hide gelatin Indonesia. (Animal Production 12(3): 190-198 (2010)Â Key Words: traceability, institutional model, cattle hide, gelatin